Effect of Performance Appraisal on Employee Productivity at Jollibee- Novaliches, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Every employee’s individual performance influences the entire team or even the firm. It alsoclarifies the employee’s role and status in the organization. Performance appraisal allowsyou to provide either positive or negative feedback as well as identify areas for improvement.If the appraisal of the job employees is lower than their expectation, they will reduceattendance with lower performance and even quit the job, which is the last thing that themanagers expect.Assessment of Performance Appraisal given on Employee in terms of Evaluative: The firststatement has a weighted mean of 3.48, which is the highest, while the fourth statement hasa weighted mean of 3.32, which is the lowest. Cognitive: The first statement has a weightedmean of 3.50, which is the highest, while the fourth statement has a weighted mean of 3.36,which is the lowest. Behavioral: The first statement has a weighted mean of 3.50, which isthe highest, while the fourth statement has a weighted mean of 3.18, which is the lowest.Factors that affect Employee Productivity in terms of Skills Acquisition: The first statementhas a weighted mean of 3.62, which is the highest, while the fourth statement has aweighted mean of 3.34, which is the lowest. Motivation: The first statement has a weightedmean of 3.62, which is the highest, while the fourth statement has a weighted mean of 3.36,which is the lowest. Leadership: The first statement has a weighted mean of 3.58, which isthe highest, while the fourth statement has a weighted mean of 3.52, which is the lowest.It is a must to provide more learning opportunities to their employees. Improvingperformance and productivity are not the only things that can benefit employee learning, andmaking knowledge out of it is also part of the opportunities that employees can get ifprovided. At this time, not all employees can get knowledge without having someone helpthem get it; on the contrary, to get that kind of opportunity, the employee must have thequalifications to do so.
Keywords: Business Administration